A comparision between blood glucose concentration measured in capillary and venous blood using glucometer and measurements in venous plasma using Auto analyser - Omar, Tahani Y. (Journal of Medical Sciences, 2022)
There are several methods for laboratory measurement of blood glucose. The detection, identification and quantification of glucose in blood has played a vital role in the diagnosis and management of patients suffering from disorders of carbohydrate metabolism and is one of the most frequently performed determinations in clinical chemistry. Aim: The purpose of this study is to the Compar between different methods of blood glucose estimations in venous whole blood, capillary whole blood by glucometer, and plasma glucose estimation by Auto analyser. Materials and Methods: A 60 adult patients were randomly selected and included in the study, to measure the blood glucose. Blood samples were collected from all persons (fasting 10/12-hour overnight), whether a known case of diabetes or not. Venous whole blood glucose, Capillary whole (Finger prick) blood glucose estimation was done by glucometer; and venous plasma glucose estimation was done by auto analyzer in laboratory. Results: Means of Venous Whole blood glucose level measurements and finger-prick blood glucose level measurements were the highest, 146.63±10.16 mg/dL and 143.80±9.73 mg/dL, respectively, which indicates that the means were higher than that of Venous plasma glucose level measurements, but this rise was statistically insignificant when compared to the Venous plasma glucose level measurements 120.67±8.88 mg/dL. The percentage statistically insignificant elevations of blood glucose concentrations in capillary whole blood and venous Whole blood were 19.17 % and 21.51% respectively when compared with the control value( plasma blood glucose). Conclusion: Capillary blood glucose estimation by glucometer is a faster method for glucose estimation , provided that the device used for the measurement is calibrated according to the manufacturer's conditions, but the main controversial issue is the reliability of glucometers, as they may show large deviations. However, a degree of caution should be exercised in the interpretation of bedside glucometer measurements as they may not be sufficiently accurate to replace laboratory blood glucose results.As the study includes 60 sampl only, a larger study is necessary for authentication of the findings. Although, many studies also show the same results. Future research with a larger sample size should be done.